PROMOTIONAL STRATEGY OF STARCROSS COMPANY - , AMINOVA OKTAVANI, Mr. Supriyono, S.S., M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Starcross is one of distro in Yogyakarta. Built the store in 2009, Starcrossuses many strategies to get the consumers and to increases its sales. However, the store has not known yet which strategy is the most effective in the way of attracting consumersâ attention. The first aim of this graduating paper is to find out the promotional strategies of Starcross Store. The next aim is to find out the effectiveness of each promotional strategy. Methods of collecting data are direct observation and library research. In the field study, the writer interviews the manager of Starcross Store in order to gather information about Starcrossâs profile in brief. For the library research, the writer reads some books, and articles from internet, which are related to the topic. Each productwhich isoffered by the store got a full attention from public. It is proven from the increasing of sales after some promotion are done. From data the author got from the store